COVID-19 Related Practices in a Remote Rural Municipality of Nepal – an Observational Study - Jha, Jay Prakash; Panta, Prem Prasad (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Health promotion, specific preventive measures, disease screening and timely isolation are the mainstay for controlling the spread of COVID-19 infection. This study is conducted in a remote place of Nepal to describe the various preventive measures practised by the community for COVID prevention and general health fitness. Methods: An observational study was conducted in Guthichaur Rural Municipality (RM) of Jumla. The subjects were tested for antigens by Rapid Diagnostic Test (RDT) kit for COVID-19 infection. Subjects were evaluated with a questionnaire to assess the awareness and practices related to COVID prevention and health promotion, including Yogasan and Pranayam. Data were analyzed by descriptive (mean and standard deviation) and inferential (Chi-Square test) statistics.Results: A total of 546 subjects were tested for COVID, 49 were positive by RDT (case positivity rate 9%). Among them, 218 were evaluated by questionnaire. The mean age was 40.39 years (range 5 – 81). The sex ratio was 1.9, favouring males; but females were more (58%) among COVID positive. Common complaints were headache (39.4%), fever (33.3%), dry cough (24.2%) and body ache (24.2%). There were significantly higher positive subjects who had contact with COVID-19 positive individuals within the past 14 days (p